Meninjau Perilaku Kerja di Lembaga Pendidikan: Studi Literatur pada Perilaku Inovatif Guru dan Tenaga Kependidikan - Pratama, Linardo; Setiyadi, Bradley; Pratiwi, Diah Adinda (FKIP Universitas Wisnuwardhana, 2022)
Teachers and education staff need to have innovative work behavior so that educational goals can be achieved optimally. Innovative work behavior studies in Indonesia are more dominant in detail in organizations that produce products or companies. The purpose of this research is to analyze what variables affect and are influenced by innovative work behavior variables in educational institutions and aims to find out the forms of innovation carried out by teachers and education staff in carrying out teaching and learning activities. This research method uses literature review. Based on the results of the study, twelve variables were found that influenced the innovative work behavior of teachers or education staff. The twelfth variable is an intervention variable to see innovative work behavior. Innovative work behavior variables affect two variables, namely performance and Organizational Citizenship Behavior (OCB). Innovative work behavior is also an intervening variable from hard skills, soft skills, learning organization and motivation variables that affect performance. In addition, teacher innovation behavior was also found in carrying out learning.